Production of barueiro seedlings in different substrates - Alves, Naiara Ferreira; Costa, Ana Claudia; Alvarenga, Júlio Miguel (Scientia Agraria Paranaensis, 2021)
Barueiro (Dipteryx alata Vog.) is one of the species native to the Brazilian cerrado that has economic potential. Thus, for the implantation of commercial orchards of this fruit tree, it is important to produce quality seedlings. This study aimed to evaluate the growth of barueiro seedlings under different substrates containing organic residues in the municipality of Nova Xavantina-MT. The experimental design used was randomized blocks (RBD), with 7 treatments (soil (control); soil + bovine manure (2: 1); soil + coffee husk (3: 1); soil + humus (2: 1); soil + coffee husk + humus (3: 1: 1); soil + coffee husk + bovine manure (3: 1: 1); and soil + humus + bovine manure (3: 1: 1)) and 4 replicates, with ten plants per plot, totaling 280 seedlings. Treatments consisted of substrates formulated with different proportions of soil, bovine manure, coffee husk and earthworm humus. Substrate containing only soil (control) provided greater plant height, stem diameter, number of leaves, number of leaflets, shoot and root fresh and dry mass and Dickson Quality Index. In general, residues tested did not favor the growth parameters evaluated, possibly because barueiro is a species native to the Cerrado, not very demanding in soil fertility. Under the conditions of this work, it is recommended the use of soil in the formulation of substrates to produce barueiro seedlings. The addition of organic matter to the soil had negative effect on seedling development.